Aterros com terra preta arqueológica em várzeas do Alto Solimões - AM - Silva, Francisco Santos da (Brasil, 2022)
In the Várzea and Terra Firme ecosystems there are soils with an anthropic horizon, known as: Terra Preta de Indio (TPI), Terra Preta (TP), Terra Preta Arqueológica (TPA) or Archeo-Antrosol. They are dark colored soils with fragments of ceramics and/or lithic artifacts, high levels of organic matter and high fertility that do not seem to wear out over time. Research on TPA is concentrated in the Middle and Lower Amazon region, and few studies focus on TPAs in the upper Solimões. Thus, the objective was to understand the genesis, physical, chemical and mineralogical attributes of the Archaeological Black Lands in a pedoenvironment of Várzea in the municipalities of Amaturá and São Paulo de Olivença, in the Alto region. Trenches will be opened in TPAs and adjacent soils, for morphological description and sample collection. Soils will be classified accordingly. Samples will be prepared in air-dried fine earth (TFSA). The TFSA will carry out granulometric and routine chemical analysis, which are separation and quantification of sand, silt and clay fractions, active acidity (pH), exchangeable calcium (Ca2 troc trocé+), pot (K+), available phosphorus (P), exchangeable acidity (Al3+), potential acidity (H+ + Al3+) and total organic carbon (C). With the results of the chemical analysis, sum of bases (SB), tationic exchange capacity CTC, effective cation exchange capacity (t), percentage of base saturation (V) and elumímí portion percentage (V) will be calculated. This work expands the studies carried out by Miranda (2018) and contributes to the presentation of new practically unknown sites in Brazilian Pedoarcheology, in an environment of Várzea, in the Alto Solimões/A region. The soils are found on the banks of the Solimões, Jacurapá and Santo Antônio do Içá rivers in the floodplain areas (mounds), with ceramic fragments being found everywhere and with a high level of fertility.